Ocular myiasis caused by Chrysomya bezziana – a case report - Nene AS (Dove Medical Press, 2015)
Amit S Nene, Anoop Mishra, Purnima Dhand Department of Ophthalmology, Assam Medical College and Hospital, Dibrugarh, Assam, India Abstract: Ophthalmomyiasis can have variable presentation depending on the type of fly, structures involved, and level of penetration. A 42-year-old female presented with extensive myiasis of the right eye. A lesion of 3×2 cm was noted at the medial canthus and was infested with maggots. The larvae were removed meticulously and the wound debrided. The larva isolated was that of Chrysomya bezziana (Old World screwworm). Computed tomography (CT) scan was normal. The wound was dressed regularly and healed by secondary intention. Ocular myiasis is a rare disease that can lead to life threatening consequences, such as intracranial extension. Prompt management with debridement and radical antibiotic therapy is essential. Keywords: ophthalmomyiasis, medial canthus, screwworm